Foreign Locals: Myth or Reality - Saleem, Farida (Journal of Ecohumanism, 2024)
Multinational corporations depend predominantly on staff from the country where their international operations are, yet more international business literature is needed to target these employees. The literature has referred to them as “host-country nationals” (HCNs), and this label gives them an individuality strongly related to their home country's culture. Caprar (2011) identified these HCNs as foreign locals. This study examines the impact of four cultural dimensions, i.e., power distance, masculinity vs. femininity, individualism vs. collectivism, and uncertainty avoidance, on employee’s perceived performance and innovativeness and how the foreign locals influence this impact as a moderator. Data were collected from Pakistani employees working in one Pakistani and one Norwegian-based MNE (multinational enterprise). The structural Equation Modeling technique using the maximum likelihood method was used for data analysis. Results show that foreign locals moderate the proposed relationships. These relationships are less stronger and/or insignificant for Pakistani employees working in Pakistani organizations and are significant and/or more-stronger for Pakistani employees working in Norwegian MNE.